Fostering Children to Have Environmental Love Behavior in Facing Climate Change at Densely Population Urban Area - Rusdi Hasan; Tia Setiawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Cibunut is a densely populated urban area at the center of Bandung City, West Java. This village has been chosen by the district government as a pro-climate area, but this policy was little known to children. This socialization aimed to provide knowledge and foster pro-environmental behavior in children as early as possible so that the values that the children obtained were internalized independently and would have an impact on a sustainable lifestyle after adulthood as a form of mitigation against climate change. This socialization activity used the creative educational approach, namely insight, role models, and conditioning. The results of this activity not only provided knowledge about the impact of supporting cleanliness but also increased the children's motivation to take part in environmental love activities. During the socialization, children were challenged to practice environmentally friendly behavior together. This enjoyable education approach in community service was able to foster children who care about environmental issues can be seen from their awareness of the environment and climate change, ready to contribute toward keeping a clean and sustainable environment.